SEMINAR AND WORKSHOP IN THE MANAGEMENT OF ALLERGIC RHINITS AND RHINOSINUSITIS IN JEMBER, EAST JAVA - Dwi Reno Pawarti; Budi Sutikno; Elsa Rosalina; Puguh Setyo Nugroho; Nindya Shinta Rumastika; Irma Zakina; Edwin Hidayat (Universitas Airlangga, 2023)
Allergic rhinitis and rhinosinusitis are global problems that are frequently encountered in daily clinical practice. This disease has an impact on the quality of life of sufferers who can resulting in decreased productivity, interpersonal relationships, and social activities. Socialization is needed regarding allergic rhinitis and rhinosinusitis so that medical personnel can participate in early diagnosis and management of allergic rhinitis and rhinosinusitis. Educational activities are carried out through outreach activities using lecture methods, discussions, training, as well as pretest and posttest. Based on the results of the pretest and posttest, the pretest average was 56,55 (± 27.51) and the posttest average was 89.27 (±12.95). Based on the comparison of pretest and posttest results, we found a statistically significant difference (p < 0.05). Medical personnel's knowledge of allergic rhinitis and rhinosinusitis needs to be increased so that they can participate in early diagnosis and management of allergic rhinitis and rhinosinusitis.